THE EFFECTIVENESS AND COST ANALYSIS OF ZINC TREATMENT ON THE CHILDREN WITH ACUTE DIARRHEA IN PKU MUHAMMADIYAH YOGYAKARTA HOSPITAL IN 2011 - Sudewi Mukaromah Khoirunnisa; Tri Murti Andayani; Inayati Inayati (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Diarrhea is the second leading cause of death among children in the world and medical cost to deal with diarrhea is significantly high. WHO and UNICEF recommend the use of zinc to treat diarrhea on children. This research was aimed to assess of diarrhea the influence of giving zinc supplement on the duration, length of stay and frequency, and to identify the amount of direct medical cost borne by the patient who used utilizing zinc in order to treat diarrhea. This research was conducted with non-experimental descriptive design. Data were taken retrospectively from medical record and financial office of PKU Muhammadiyah Yogyakarta Hospital. The research subjects were child patients aged 1 - < 15 years old suffering from acute diarrhea, used antibiotic, had no other diseases, and treated as inpatient during the period of January 1 until December 31st 2011. The number of samples that met the inclusion criteria were 67 patients for each zinc and control group. The data were analyzed based on the characteristics of patients, diarrhea duration in the hospital, length of stay, diarrhea frequency and amount of medical cost. Data were analyzed descriptive quantitatively and statistically to compare the means of variables between both groups. The research result indicated that the group receiving zinc had shorter diarrhea duration of ±0.45 day (p<0.05), shorter length of stay of ±0.09 day (p>0.05), and lower diarrhea frequency from the second to the fourth day of the treatment (p<0.05). In regard to cost analysis, the total medical cost of zinc group was lower than that of control group (p<0.05) accounts for IDR. 1,155,407. However, it could not be concluded that the use of Zinc was effective. The use of zinc was effective in treating acute diarrhea on inpatients children.Keywords: zinc, acute diarrhea, effectiveness, direct medical cost